Evaluation of the Efficacy and Safety of DW1903 in Patients with Gastritis: A Randomized, Double-Blind, Noninferiority, Multicenter, Phase 3 study - Jie-Hyun Kim; Hwoon-Yong Jung; In Kyung Yoo; Seon-Young Park; Jae Gyu Kim; Jae Kyu Sung; Jin Seok Jang; Gab Jin Cheon; Kyoung Oh Kim; Tae Oh Kim; Soo Teik Lee; Kwang Bum Cho; et al. (Gut and Liver, 2024)
Background/Aims: H2 receptor antagonists (H2RA) have been used to treat gastritis by inhibiting gastric acid. Proton pump inhibitors (PPIs) are more potent acid suppressants than H2RA. However, the efficacy and safety of low-dose PPI for treating gastritis remain unclear. The aim was to investigate the efficacy and safety of low-dose PPI for treating gastritis. Methods: A double-blind, noninferiority, multicenter, phase 3 clinical trial randomly assigned 476 patients with endoscopic erosive gastritis to a group using esomeprazole 10 mg (DW1903) daily and a group using famotidine 20 mg (DW1903R1) daily for 2 weeks. The full-analysis set included 319 patients (DW1903, n=159; DW1903R1, n=160) and the per-protocol set included 298 patients (DW1903, n=147; DW1903R1, n=151). The primary endpoint (erosion improvement rate) and secondary endpoint (erosion and edema cure rates, improvement rates of hemorrhage, erythema, and symptoms) were assessed after the treatment. Adverse events were compared. Results: According to the full-analysis set, the erosion improvement rates in the DW1903 and DW1903R1 groups were 59.8% and 58.8%, respectively. According to the per-protocol analysis, the erosion improvement rates in the DW1903 and DW1903R1 groups were 61.9% and 59.6%, respectively. Secondary endpoints were not significantly different between two groups except that the hemorrhagic improvement rate was higher in DW1903 with statistical tendency. The number of adverse events were not statistically different. Conclusions: DW1903 of a low-dose PPI was not inferior to DW1903R1 of H2RA. Thus, lowdose PPI can be a novel option for treating gastritis (ClinicalTrials.gov Identifier: NCT05163756).